Perspektif Nasabah Terhadap KUR Di Bank BRI Tanjung - Finda Desi Lutfiana; Hifna Rizqiyani Maulida; Munir Is’adi (CV. ITTC INDONESIA, 2023)
Microenterprise Credit (MEC) has emerged as a pivotal instrument in fostering socio-economic development, particularly in empowering marginalized communities worldwide. In Indonesia, Bank Rakyat Indonesia (BRI) has played a significant role in extending Microenterprise Credit to empower small-scale entrepreneurs through its Kredit Usaha Rakyat (KUR) program. This abstract aims to provide an overview of the KUR program administered by BRI, focusing on its impact, challenges, and future prospects. The study employs a qualitative approach, drawing insights from existing literature, official reports, and interviews with key stakeholders. The KUR program of BRI has significantly contributed to enhancing financial inclusion by providing accessible and affordable credit facilities to microentrepreneurs, especially in rural and remote areas. Through this program, BRI has facilitated entrepreneurship development, job creation, and poverty alleviation, thereby fostering inclusive economic growth